The role of arabic poetry in national security: a case study of umayyad period (2010)
Poetry where like in other culture is deep-rooted in the life of the Arabs. It has once given of tribal community of blood ties which was regarded sacred and the basis of a National Community. The rapid rate of the political parties in the Umayyad age had a great impact on the poetry of the then poets, which made the parties have their poets defending their parties and also expressing their feelings about the societal ills. Thus, this paper is aimed at bringing to the limelight the impact of political poetry on the national security of the people. Also, the paper shall properly dealt with historical account of political icons in Umayyad age and their poetry will be appraised for the purpose of highlighting their literary worth.